Distribution pattern of hepatitis C virus in eastern peninsular Malaysia for the past decade - Hasmoni, Mohamed Hadzri; Jaafar, Khairul Azhar; Che Aun, Azlida; Tee, Hoi Poh (Wiley Publishing Asia Pty Ltd, 2015)
Introduction: Analysis of the Hepatitis C Virus (HCV) genotype spread in a particular area has a crucial impact on public health. Genotyping is essential before initiating treatment.